HYDRODISSECTION FOR PRESERVATION OF NEUROVASCULAR BUNDLE DURING RADICAL PROSTATECTOMY - H. S. Gevorgyan; A. A. Kostin; N. V. Vorobyev; P. V. Shegai (Исследования и практика в медицине)
Nerve-sparing radical prostatectomy is one of the high-tech operations in urology, and the challenge of the surgeon is not only to remove the prostate tumor, but also to provide a high quality of life. The fact that most questions devoted from patients in a conversation with the surgeon before the operation are devoted to this issue, shows the importance and relevance. At present, the diagnostic methods allow significantly more likely to detect early  prostate cancer, making finding and treatment of these patients more affordable and allows to apply this operation.Lately, it seems urgent to explore the possibility of water jet dissection in the field of urology, in particular, for nerve-sparing prostatectomy. Preservation of erectile function depends largely on the quality of separating the neurovascular bundle. Standard use of electrocautery is associated with damage to the neurovascular bundle.  When performing operations using water-jet mobilization of prostate the selective dissection of tissue is performed. This avoids injury of neurovascular bundle and further postoperative complications. The use of this technique may allow the surgeon to provide a more accurate mobilization prostate and selectively controlled intersection vessels heading to the prostate from the neurovascular bundle, reduce intraoperative blood loss,  maintaining continence, erectile function.This literature review is considered by the experience of using nerve-sparing radical prostatectomy using a water-jet dissector, estimated intraoperative parameters using this method.However, we have the lack of extensive research capabilities of this technique when performing nerve-preserving radical prostatectomy, that does not allow to make a comprehensive presentation on the benefits of this technique and its effects on erectile function and quality of urination, further study of this issue in such a difficult category of patients.